Local Wisdom of Settlement Growth in theUrban Fringe Areas - Setioko, Bambang (RUAS, 2011)
The population growth in the urban fringe area of developed countries is dominated by the urban sprawl and followed by â€œwhite flight phenomenaâ€. In Indonesia, although the physically growth of settlements is similar, but the socially one is different. The modern housing estates have been built in the next to the rural settlements. In addition, the autonomous settlements have been emerged surrounding housing estates; the spread settlements will integrate in the following years. This research has been done with the qualitative methods and successfully revealing the existence of local wisdomof settlement growth in Semarang fringe area.Keywords: fringe area, urban sprawl, white flight, local wisdom